Dinâmica espaço-temporal da cobertura de Mata Atlântica no Centro de Endemismo Pernambuco e uso do habitat pela avifauna ameaçada da região - Dias, Thiago da Costa (Universidade Federal de São Carlos, 2023)
The Atlantic Forest is one of the world's most important biodiversity hotspots, harboring a high species richness and serving as the stage for some of the largest conservation challenges nowadays. A small portion of this biome located in northeastern Brazil, known as the Pernambuco Endemism Center (PEC), stands out for hosting a high concentration of threatened and restricted-distribution species. The irreplaceable ecosystems of the PEC have been continuously affected by deforestation, fragmentation, degradation, and defaunation, resulting in the loss of many crucial ecological relationships that maintain biodiversity. It is essential to promote management and conservation actions for species and habitats in the PEC to prevent anticipated species losses in the region. Across the PEC, investigating historical changes and the current state of forest habitats, and characterizing space use and distribution by its threatened wildlife may guide conservation efforts and assist decision-making focused on landscape management. Therefore, this study aimed to characterize the spatiotemporal dynamics of the forest cover in the PEC over the past 35 years (1985-2020) by (i) assessing trends in biomass accumulation/loss in remnants of native vegetation and (ii) identifying changes in the spatial configuration and distribution of forest habitats in the region. The study additionally intends to (iii) reveal the distribution, richness, key resources/habitats, and areas of high ecological relevance for the endemic and threatened avifauna of the PEC, ultimately proposing the creation of ecological corridors as a tool for biodiversity conservation. The condition of the PEC’s forest cover is alarming, and although biomass accumulation (greening) and improvements in metrics related to habitat quality were identified over the last decades, factors such as the reduced size of the fragments, severe edge effects, and the replacement of mature by secondary vegetation are current threats for the local biodiversity. The persistence of endemic and threatened birds in the PEC may rely on energetic and large-scale conservation strategies and landscape management, and here we propose the creation of the Pernambuco Endemism Center Restoration Arc (PEC- ARC), which may be able to connect fragments with high ecological relevance through forest restoration initiatives. Together with the ongoing conservation actions that became increasingly important to the PEC over the last years, this strategy may provide critical improvements in habitat quality over the region, increase gene flow and organismal movement, promote habitat recolonization, and ensure population adaptability to climate change, which may ultimately reduce the risks of future global extinctions expected for the region.
Spatiotemporal dynamics of the Atlantic Forest cover in the Pernambuco Endemism Center and habitat use by its endangered birds
Keywords: Paisagens modificadas pelo homem; Ecologia da paisagem; Modelagem de distribuição de espécies; Áreas prioritárias para conservação; Human-modified landscapes; Landscape ecology; Species distribution modeling; Conservation priority areas; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES